The roles of lipid and glucose metabolism in modulation of β-amyloid, tau, and neurodegeneration in the pathogenesis of Alzheimer disease - Sato, Naoyuki; Morishita, Ryuichi (Frontiers in Aging Neuroscience, 2015)
Diabetes is a risk factor for Alzheimer disease (AD). Apolipoprotein E (ApoE) and several genes related to AD have recently been identified by genome-wide association studies as being closely linked to lipid metabolism. Lipid metabolism and glucose-energy metabolism are closely related. Here, we review the emerging evidence regarding the roles of lipid and glucose metabolism in the modulation of β-amyloid, tau, and neurodegeneration during the pathogenesis of AD. Disruption of homeostasis of lipid and glucose metabolism affects production and clearance of β-amyloid and tau phosphorylation, and induces neurodegeneration. A more integrated understanding of the interactions among lipid, glucose, and protein metabolism is required to elucidate the pathogenesis of AD and to develop next-generation therapeutic options.